A Look From the Forensic Medicine at a Family whose Member’s Lives Has Changed with the Carbon Monoxide Poisoning Not Resulted in Death - Karbeyaz, Kenan; Gündüz, Tarık; Kul, Gülşin Canoğulları; Balcı, Yasemin (The Bulletin of Legal Medicine, 2009)
Carbon monoxide (CO) is an odorless, colorless, tasteless gaseous with no irritant property and which is formed due to lack of the oxidation of materials including carbon. Carbon monoxide poisoning, which is a very important problem for the public health, is very common in our country, and it is a very important cause of morbidity in winter months. Carbon monoxide poisonings, sometimes resulting in death, is very important for forensic medicine. This presented case is related with carbon monoxide poisonings of three members of a four-member family, who works as janitors in an apartment building, and as a heating system employee in another apartment building in Eskişehir, in a two-week time lapse. The case developed when the father, who works as a janitor and heating system employee, was found fainted first time, together with his 4-four year old daughter, and second time together with his 12-year-old son in front of the heating boiler of the apartment he worked. This case has been considered to be important to present and discuss, because, it took place in a workplace, is a repeated case and related with the father’s negligence and carelessness. It is thought that presenting these kinds of cases to be discussed will contribute to medical applications. Key words: Carbon monoxide poisoning, complication, forensic medicine